ANALISIS KONTRIBUSI PAJAK PARKIR DAN PAJAK RESTORAN DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) JAKARTA TIMUR SERTA KONTRIBUSI TERHADAP PENDAPATAN ASLI DAERAH (PAD) DKI JAKARTA DALAM SEKTOR PAJAK PARKIR DAN PAJAK RESTORAN - Mulia Rahmah, SKom., M.Si.; Rina Hidayahti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This research is to find out how big the tax contribution of parking and restaurant in order to increase tax Income Native (PAD) in East Jakarta, as well as how large the tax contribution of parking and restaurant Tax Revenue against the Original East Jakarta area (PAD) DKI Jakarta in the tax sector, parking and restaurant tax. This research was conducted at the Suku Badan Pajak dan Retribusi Daerah. This research is a qualitative descriptive study. Data taken from the Regional Original Revenue Report (PAD) in the form of targets and realization of East Jakarta's parking tax and restaurant tax 2015-2017. The analysis used is descriptive analysis using the ratio of parking tax contribution and restaurant tax. Data collection in the study was obtained from observation, interviews and documentation. The conclusion of this study, shows that the average contribution given Parking Tax and Restaurant Tax in order to increase the East Jakarta Regional Original Revenue (PAD) in 2015-2017 is 0.88% for Parking Tax with the criteria of